A Combined Experimental and Analytical Approach for the Simulation of the Sound Transmission Loss of Multilayer Glazing Systems. (November 2015) - Ruggeri, Paolo; Peron, Fabio; Granzotto, Nicola; Bonfiglio, Paolo
Abstract: High sound insulation façade requirements in contemporary buildings, led to the development of high-performance multilayer glazing systems. In this work a combined experimental and analytical approach has been adopted to predict the sound transmission loss of systems made of glass and PVB layers, which are used in several engineering areas (building, transportation, etc.). In particular, the mechanical properties of glazing systems have been measured using resonance curve method of flexural waves on multilayer glass beams with different boundary conditions. In order to achieve reliable input mechanical data (Young's modulus and loss factor) the beams are characterized in free-free and clamped-clamped boundary conditions respectively. Moreover, the diffuse field sound transmission loss of glass panels has been predicted through an analytical method for solid elastic layers. Results from the above-mentioned procedure have been compared with laboratory tests carried out according to ISO Standard 10140 series.